The Role of Budget for Operational Assistance (BOS) Fund Management in Supporting Quality Learning at MTs Al-Hasan Banjarsari - Hardian, Dafyar Eliadi; Muhit, Abdul; Kusuma, Dian; Rusdiyansyah, Rusdiyansyah; Yuliasih, Yuliasih (Transpublika Publisher, 2026)
The Budget for Operational Assistance (BOS) aims to improve access to and quality of education through operational funding support for schools, but its effectiveness is still influenced by transparency, accountability, and efficiency in its management. This study aims to analyze the role of Budget for Operational Assistance (BOS) fund management in improving the quality of learning at MTs Al-Hasan Banjarsari, Ciamis Regency. The research focuses on five key management aspects: planning, organizing, implementing, monitoring, and evaluating. The method used in this study is descriptive qualitative. Data collection was conducted through interviews, observation, and document analysis. Informants involved in this study included the Madrasah Principal, Deputy Madrasah Principal, treasurer, teachers, school committee members, supervisors, and the BOS Management Team from the Ministry of Religious Affairs of Ciamis Regency. The research findings indicate that BOS fund management at the madrasah is transparent and involves various parties. The funds are used to support teaching and learning activities and improve educational facilities. This success is driven by the leadership of the madrasah principal, alignment between the program and the school’s vision, and collaboration with various parties. However, several challenges remain, such as delays in fund disbursement, a lack of technical personnel, and low community participation in financial assistance. Therefore, it is necessary to strengthen the management system and increase cooperation between parties so that the use of BOS funds can be more effective in improving the quality of education.